Implementation of Web-Based Waterfall Method Case Study Information System Complaints of Violence Women and Children - Syahril Andika Siregar; Deci Irmayani; Musthafa Haris Munandar (Jurnal Mantik, 2021)
Violence is any act of abuse of physical strength with or without the use of means against the law and causing harm to the body, life and freedom of people. Violence against women and children is a violation of human rights that can happen to anyone, across social, economic and educational status. The process of complaints of violence against women and children, which is currently mostly carried out, is still manual with victims / communities coming directly to the complaint center to make a complaint report. To support the research, the method used in making the Information System for Complaints on Violence against Women and Children is waterfall and the UML model used is the Php programming language, MySql Database, Boostrap, Sublime Text. The results of the study resulted in the implementation of complaints of violence against women and children based on reports of victims / communities affected by violence. Data on complaints of violence against women and children. can provide complete and accurate information in accordance with the complaint desired by the victim and printed as the last step in the process of managing victim complaint data.